2023
DOI: 10.21037/atm-23-1404
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance and distribution of Helicobacter pylori virulence factors in isolates from Chinese patients

Abstract: Background At present, the relationship between virulence factors of Helicobacter pylori ( H. pylori ) and gastrointestinal diseases is still under discussion. This study investigated the association between distinct virulence factors in H. pylori and different gastrointestinal diseases. Methods Gastric biopsy specimens were obtained from 160 patients with different gastrointestinal disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Consistent with previous findings, our study demonstrated an increase in AUF1 expression in both gastric epithelial cells and gastric mucosal tissue of patients with chronic superficial gastritis infected with CagA-positive H. pylori ( Figure 7 ). Although we did not conduct a biopsy typing test for CagA in the gastric mucosa of H. pylori -infected patients, recent studies in China have reported a prevalence of CagA-positive H. pylori strains ranging from 97% to 100%, 56 , 57 suggesting that the majority of H. pylori strains infecting our study participants were CagA-positive. Furthermore, we found that both exogenous CagA and CagA-positive H. pylori infection can induce the translocation of AUF1 from the nucleus to the cytoplasm.…”
Section: Discussionmentioning
confidence: 87%
“…Consistent with previous findings, our study demonstrated an increase in AUF1 expression in both gastric epithelial cells and gastric mucosal tissue of patients with chronic superficial gastritis infected with CagA-positive H. pylori ( Figure 7 ). Although we did not conduct a biopsy typing test for CagA in the gastric mucosa of H. pylori -infected patients, recent studies in China have reported a prevalence of CagA-positive H. pylori strains ranging from 97% to 100%, 56 , 57 suggesting that the majority of H. pylori strains infecting our study participants were CagA-positive. Furthermore, we found that both exogenous CagA and CagA-positive H. pylori infection can induce the translocation of AUF1 from the nucleus to the cytoplasm.…”
Section: Discussionmentioning
confidence: 87%